Merayakan Hari Kenaikan Yesus Kristus Berdasar Perspektif Pembaruan Liturgi di Kalangan Protestan - Apriano, Alvian (P3M STT Kristus Alfa Omega, 2024)
This study explores the spirit of liturgical renewal as a basis for reconstructing worship models on church feast days in Protestant congregations, focusing on one often overlooked feast, the Ascension of Jesus Christ. This study questions whether the spirit of liturgical renewal can create worship models and liturgical orders for this celebration that enhance congregational appreciation during Ascension services. It aims to propose a worship model for the celebration of the Ascension of Jesus Christ that involves situational reflection, active congregational participation, and the integration of technology in worship by using literature review method.